Using About-Point Strategy to Improve the Hortatory Exposition Text Reading Skill of the Eleventh Graders of SMA Muhammadiyah 1 Kota Magelang in the School Year 2018/2019. - Whendy Dwi Januar Indah Pratiwi (Faculty of Education and Teachers Training, 2020)
Reading is one of basic skills that are important for the students. Because by reading, the students will get the information based on the text that they have read. Based on the observation, students still find difficulties in determine main idea and supporting details of the text.The objectives of this research are; first, is to explain whether About-Point strategy can improve the students’ learning motivation of the hortatory exposition text reading skill. The second is to describe how great is the improvement of the students’ reading skill taught by About-Point strategy.The researcher conducted a CAR (Classroom Action Research). It was divided into three phases; they are Pre-Cycle, Cycle I, and Cycle II. The researcher took XI PA 2 students of SMA Muhammadiyah 1 Kota Magelang in the school year 2018/2019 as the subject of this research.There was a good improvement of the students after the researcher taught by using About-Point strategy. They were curious and active in learning process of hortatory exposition text reading skill because they wanted to improve their reading skill.The result of the test showed that their score improved. In the Pre-Cycle their average score in reading test was 64.40, and in Cycle I, their average score was improved and reached 70.00. It means that they were any improvement of their score from the pre cycle to cycle I. The average score of reading test in Cycle II is 79.00 and it means they were motivated by using the strategy.